2023
DOI: 10.1177/17474930231205221
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of imaging markers adjusted for time since symptom onset in intracerebral hemorrhage: A novel predictor for hematoma expansion

Lei Song,
Jun Cheng,
Cun Zhang
et al.

Abstract: Background: Hematoma expansion (HE) is common in patients with intracerebral hemorrhage (ICH), and associated with a worse outcome. Imaging makers and shorter time from symptom onset are both associated with HE, but prognostic scores based on these parameters individually have not been satisfactory. We hypothesized that a score including both imaging markers of expansion, and time of onset, would improve prediction. Methods: Patients with supratentorial ICH within 6 h after onset were consecutively recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Surprisingly, the prediction performance did not significantly reduce based on the definition of RHE compared with the conventional definition of hematoma expansion (AUC = 0.80 vs. 0.83). 7 The findings of our study complement the influence of FIM on IVH growth and RHE, and facilitate stroke physicians identify individuals with a high-risk of hemorrhagic growth who may benefit from early intervention.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Surprisingly, the prediction performance did not significantly reduce based on the definition of RHE compared with the conventional definition of hematoma expansion (AUC = 0.80 vs. 0.83). 7 The findings of our study complement the influence of FIM on IVH growth and RHE, and facilitate stroke physicians identify individuals with a high-risk of hemorrhagic growth who may benefit from early intervention.…”
Section: Discussionsupporting
confidence: 56%
“…The search for imaging markers that could predict the risk of hemorrhagic growth after ICH has been a hot research topic, such as density and shape features on non-contrast CT. 16,17 Although attractive, the predictive performance of a single sign usually does not perform well. 17 A first proposal for FIM in 2023 was by Song et al, 7 which is defined as the ratio of imaging markers to onset-to-CT time. They found that the novel index positively predicts hematoma expansion, with a good performance when the optimal FIM cutoff value is 0.63.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indicator of frequency of imaging markers (FIM), which is regarded as an independent predictor of HE, was rst proposed by Song et al in 2023 [7]. There is likely to be a link between FIM and functional neurological outcome in patients with ICH, but evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%